A Novel Role of PP2A Methylation in the Regulation of Tight Junction Assembly and Integrity - Schuhmacher, Diana; Sontag, Jean-Marie; Sontag, Estelle (Frontiers in Cell and Developmental Biology, 2022)
Tight junctions (TJs) are multiprotein complexes essential for cell polarity and the barrier function of epithelia. The major signaling molecule, protein serine/threonine phosphatase 2A (PP2A), interacts with the TJ and modulates the phosphorylation state of TJ proteins. An important PP2A regulatory mechanism involves leucine carboxyl methyltransferase-1 (LCMT1)-dependent methylation and protein phosphatase methylesterase-1 (PME1)-mediated demethylation of its catalytic subunit on Leu309. Here, using MDCK cells, we show that overexpression of LCMT1, which enhances cellular PP2A methylation, inhibits TJ formation, induces TJ ruffling, and decreases TJ barrier function. Conversely, overexpression of PME1 accelerates TJ assembly and enhances TJ barrier function. PME1-dependent PP2A demethylation increases during early Ca2+-dependent junctional assembly. Inhibition of endogenous PME1 delays the initial Ca2+-mediated redistribution of TJ proteins to cell-cell contacts and affects TJ morphology and barrier function. Manipulating one-carbon metabolism modulates TJ assembly, at least in part by affecting PP2A methylation state. The integrity of PP2A methylation is critical for proper targeting of PP2A to the TJ. It is necessary for PP2A complex formation with the TJ proteins, occludin and ZO-1, and proteins of the PAR complex, Par3 and atypical protein kinase C zeta (aPKCzeta), which play a key role in development of cell polarity. Expression of a methylation incompetent PP2A mutant induces defects in TJ assembly and barrier function. aPKCzeta-mediated Par3 phosphorylation is also required for targeting of the PP2A ABalphaC isoform to the TJ. Our findings provide the first evidence for a role of LCMT1, PME1 and PP2A methylation/demethylation processes in modulating TJ assembly and functional integrity. They also position PP2A at the interface of one-carbon metabolism and the regulation of key TJ and polarity proteins that become deregulated in many human diseases.